Spatial Analysis as a Tool for Selecting the Most Suitable Sites for Rural Spatial Development Projects Case study: Agro polis Development Project for the plain of Al-Ghab - Barakat, Tarek; Hababah, Nadim Mohammed (Latakia University Journal -Engineering Sciences Series, 2019)
The spatial development of rural areas is based on the optimal investment of natural resources (environmental and human). There is a close relationship between the development processes, the place and the environment, and this relation appears in the settlement of development projects in a way that ensures continuity for future generations and the settlement of human activity. The attraction of the Al-Ghab area for development projects since the middle of the last century until now has led to the emergence and development of scattered population groups in the countryside of this plain and along its area and the large percentage of reclaimed land. It also led to high population growth rates to exceed the national population growth rates of Syria where the population growth rate for the administrative jungle region for the period between (1970-1981) value (0.047) while it was at the level of Syria (0.034). In the absence of spatial balance of the distribution of these projects and the lack of harmony with the natural and human components where it did not take into account the appropriate spatial and specificity of the region, which led to overriding the use of agricultural land and converted to residential use and the depletion of many of the resources that contain them. The aim of this research is to assess the spatial compatibility of the comprehensive development project for the plain of the Al-Ghab through a spatial analytical methodology that seeks to preserve the natural resources of agricultural lands forests and not to build at their expense, and to link the natural environment with the reflection of its effects on human activity. The spatial analysis method takes into account the economic, physical, environmental and social factors and contributes to determining the most suitable locations for the development of rural spatial development projects. تقوم التنمية المكانية الريفية على الاستثمار الأمثل للموارد الطبيعية (البيئية والبشرية) فهناك علاقة وثيقة بين عمليات التنمية والمكان والبيئة, وهذه العلاقة تظهر في توطين مشروعات التنمية بأسلوب يضمن الاستمرارية للأجيال القادمة، وتوطين النشاط البشري. وعليه يعتبر المكان والتنمية وما ينبثق عنهما من مفاهيم وأبعاد أساس العمل التنموي وموجهاً رئيسياً له. لقد أدى جذب منطقة الغاب للمشاريع التنموية منذ منتصف القرن الماضي وحتى الآن إلى نشوء وتطور تجمعات سكانية متفرقة في ريف هذا السهل وعلى امتداد مساحته وبنسب كبيرة من الأراضي المستصلحة منه, كما وأدى إلى ارتفاع معدلات النمو السكاني لتفوق معدلات النمو القومي للسكان في سوريا حيث بلغ معدل النمو السكاني لإقليم الغاب الإداري للفترة الزمنية بين عامي (1970ـ1981) قيمة (0.047) بينما كانت على مستوى سوريا (0.034). في ظل غياب التوازن المكاني لتوزيع تلك المشاريع وعدم انسجامها مع المقومات الطبيعية والبشرية, حيث لم تأخذ بالاعتبار الملائمة المكانية وخصوصية المنطقة ما أدى إلى التعدي على الأراضي الزراعية وتحويلها للاستعمال السكني واستنزاف الكثير من الموارد التي تحويها. يهدف هذا البحث إلى تقييم الملائمة المكانية لمشروع التنمية الشاملة لسهل الغاب (الآغروبوليس) عبر منهجية تحليلية مكانية تسعى للحفاظ على الموارد الطبيعية المتمثلة بالأراضي الزراعية والغابات الحراجية وعدم البناء على حسابها، والربط بين البيئة الطبيعية وانعكاس مؤثراتها على النشاط البشري. كما يهدف لوضع تصور لتوزيع مشاريع التنمية في المواقع الأكثر ملائمة بالنظر لخصائص المكان.